Preparation of ordered mesoporous alumina particles via simple precipitation method - Ramli, Zainab; Saleh, Rozaina (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2008)
Several mesoporous alumina samples have been successfully prepared via simple and easy precipitation method by using inexpensive inorganic aluminium salts with ammonium acetate as precipitating agent. The aluminium acetate (Al(CH3COO)3) precipitate obtained was treated with nitric acid, acetone and ultrasonication to obtain mesoporous alumina. FESEM of the samples prepared from the treatment of nitric acid showed agglomeration of spherical nano- sized particle while TEM micrographs showed homogenous nano-sized pores in the range of 7-9 nm which agrees with data from nitrogen adsorption analysis. Al(CH3COO)3 treated with acetone followed by ultrasonic treatment exhibits narrower pore size distribution between 3.5-5.0 nm with higher surface area (198.36 m2/g) as compared to the sample without ultrasonic treatment. Acidity study of the alumina sample using pyridine adsorption indicates that the sample exhibits Lewis acidity